The Influence of the Cooperative Learning Model Type of Teams Games Tournaments (TGT) with the Tournament Table Game on Students' Critical Thinking Abilities - Bagus suseno; Iyan Setiawan; Rani Tania Pratiwi (International Journal of Management and Business Intelligence, 2023)
This study was to determine differences in critical thinking skills between students in the experimental class who took part in learning using the Teams Games Tournament (TGT) cooperative learning model and students in the class who took part in learning using the lecture control learning method in class XI MIPA students at SMA Negeri 2 Kuningan and the increase. In this study the method used is Quasi Experiment. The results of testing the hypothesis show that there are differences in the post test thinking skills between students who take part in learning using the Team Games, Tournament (TGT) type cooperative learning model compared to the lecture method, and there are differences in increasing critical thinking skills between students who take part in learning using the type cooperative learning model Team Gamex Tournament (TGT) compared to the lecture method. This is because the value of Tcount (1.961 and 3.968) resulting from the hypothesis test is greater than t table (1.667). Therefore, the use of the Team Games Tournament (TGT) cooperative learning model can improve students' critical thinking skills.